1958
DOI: 10.1152/ajplegacy.1958.192.2.227
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Insulin-I131 and Glucagon-I131 in the Kidney of the Rat

Abstract: Crystalline insulin or glucagon labeled with I131 was injected intravenously in adult male Sprague-Dawley rats under ether anesthesia. The left kidney was removed at intervals ranging from 10 seconds to 6 minutes following the injection, and radioautographs of histological sections were prepared. Radioactivity was found to be concentrated in the cortex of the kidney. At intervals less than 2 minutes after injection, radioactivity was prominent in the lumina of proximal convoluted tubules. At later intervals ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

1969
1969
1992
1992

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 0 publications
1
21
1
Order By: Relevance
“…As previously demonstrated [1], the urinary clearance of glucagon represents only a small percentage of the clearance of glucagon by the kidney. This observation is in agreement with earlier data which demonstrated that glucagon may be filtered through the glomerulus and reabsorbed at the tubular level [ 13]. This does not however exclude the possibility of a direct uptake from renal capillaries without previous filtration and reabsorption, as has been demonstrated for insulin [14][15].…”
Section: Insulin Uptake By the Kidney At Various Arterial Concentratisupporting
confidence: 92%
“…As previously demonstrated [1], the urinary clearance of glucagon represents only a small percentage of the clearance of glucagon by the kidney. This observation is in agreement with earlier data which demonstrated that glucagon may be filtered through the glomerulus and reabsorbed at the tubular level [ 13]. This does not however exclude the possibility of a direct uptake from renal capillaries without previous filtration and reabsorption, as has been demonstrated for insulin [14][15].…”
Section: Insulin Uptake By the Kidney At Various Arterial Concentratisupporting
confidence: 92%
“…This was confirmed with the immunoperoxidase technique. Although these findings have not been reported for PTH, localization of insulin (33)(34)(35), glucagon (36), growth hormone (37)(38)(39), luteinizing hormone, and follicle-stimulating hormone (40,41), human chorionic gonadotropin (42), and prolactin (43) (13), and our current data-showing that localization of 125I-labeled and unlabeled preparations are identical, indicate that the metabolism ofthe radioiodinated PTH used in these studies accurately reflects the metabolism of unlabeled hormone.…”
Section: Discussioncontrasting
confidence: 53%
“…The renal handling of proinsulin, insulin, and C-peptide was characterized by high extraction rates and very low urinary clearances, indicating that almost all the polypeptide removed from the circulation was sequestered or metabolized in the kidney. Kidney homogenates are known to destroy insulin in vitro (11,32), and autoradiographic studies in the rat show that labeled insulin accumulates in the cells of the proximal convoluted tubules (33,34), where it presumably undergoes degradation. It is of interest that other small molecular weight polypeptides are handled by the kidney in similar fashion.…”
Section: Resultsmentioning
confidence: 99%